(untitled) (African Journal of Biomedical Research, 2022)
We hypothesised that the calyx extract of Hibiscus sabdariffa (HS) may have antisickling potential on account of its calcium antagonistic and antioxidants effects. Five ml of blood was collected from sickle cell anaemia (SCA) patients (n=11). 50µL of blood was incubated with 50µL each of 0.l, 1 and 10mg/ml of HS before adding 50µL of 2% sodium metabisulphite (Na2S2O5) (protective assay). Also, 50µL Na2S2O5 was added to 50µL of blood and then incubated with 50µL each of 0.l, 1 and 10mg/ml of HS (reversal assay). In parallel, 50µL of blood each was incubated with 50µL of 5 mg/ml hydroxyurea and 50µL of 0.9% NaCl (control) respectively. The mean cell haemoglobin concentration (MCHC), mean cell volume (MCV) and mean platelet volume (MPV) were determined. In both the protective and reversal assays, a significant (p<0.01 and p<0.05 respectively) decrease in MCHC was observed in the presence of HS. However, there was a significant (P<0.05) increase in MCV in the presence of HS in the reversal assay only. In the protective and reversal assays the MPV increased significantly (P<0.05 and P<0.01 respectively) in the presence of HS. These parameters showed no significant change in the presence of hydroxyurea. These results suggest that in the reversal assay HS may have antisickling properties by lowering the MCHC and increasing MCV and thereby reducing haemoglobin S concentration and polymerization. This further suggests that HS may have a Gardos channel inhibitory effect. However, the increase in MPV suggests that HS may be toxic at these concentrations.